New physical and biological evidence of lateral transport affecting dinoflagellate cyst distribution in the benthic nepheloid layer along a land-sea transect off Figueira da Foz (Atlantic Iberian margin) - García-Moreiras, Iria; Hatherly, Melissa; Zonneveld, Karin; Dubert, Jesus; Nolasco, Rita; Santos, Ana Isabel; Oliveira, Anabela; Moita, Teresa; Oliveira, Paulo B.; Magalhães, Jorge M.; Amorim, Ana (Frontiers in Marine Science, 2023)
Introduction The production of resting cysts is a key dispersal and survival strategy of many dinoflagellate species. However, little is known about the role of suspended cysts in the benthic nepheloid layer (BNL) in the initiation and decline of planktonic populations. Methods In September 2019, sampling of the dinoflagellate cyst community at different water depths in the water column and in the bottom sediments, and studies of spatio-temporal changes in physical properties (temperature, salinity, density and suspended sediment concentration), were carried out along a land-sea transect off Figueira da Foz (NW Portugal) to investigate the dinoflagellate cyst distribution and the factors (physical and biological) affecting it. A clustering analysis was used to compare the BNL and sediment cyst records with the cyst rain recorded by a sediment trap at a fixed station. Furthermore, Lagrangian particle experiments enabled simulating cyst trajectories in the BNL 5 and 10 days before sampling and assessing cross-shore, vertical and alongshore transport within the studied region. Results A well-developed BNL was present during the survey, which covered a change from active (14th of September) to relaxed (19th of September) upwelling conditions. Organic-walled dinoflagellate cysts were dominant in all samples, although calcareous dinoflagellate cysts consistently occurred (at low abundances). High proportions of full cysts were observed in the BNL, of which a significant portion was viable as shown by excystment experiments. Moreover, BNL cyst records collected on the 19th of September along the land-sea transect were similar to the sediment trap cyst record but greatly differed from sediment cyst records. The heterotrophic small spiny brown cysts (SBC) and cysts of the autotrophic yessotoxin-producer Protoceratium reticulatum notably increased during the survey, in the BNL and in the water column above. Discussion The comparison of the BNL, surface sediment and sediment trap cyst records supported that the main origin of cysts in the BNL was the recent production in the water column. The spatial coincidences in the distribution of cysts and vegetative cells of Protoceratium reticulatum also supported that full cysts in the water column were being produced in surface waters. New data evidenced the presence of a significant reservoir of viable cysts in the BNL that have the potential to seed new planktonic blooms. Furthermore, back-track particle modelling evidenced that alongshore advection was the main physical mechanism controlling cyst dynamics in the BNL during most part of the survey period, being particularly intense in coastal stations (<100 m depth). Consequently, the sediment cyst signal is a mixture of locally and regionally produced cysts. We provide multi-disciplinary data evidencing that cysts recently formed in the photic zone can be laterally advected within the studied region through the BNL, contributing to a better understanding of the role of the BNL in cyst dynamics and tracing the seed sources of the new blooms.